LEGAL PROTECTION OF FRANCHISES AND FRANCHISES IN THE PERSPECTIVE OF LAW NO. 19 OF 2002 CONCERNING COPYRIGHT - Anis Nurul Aini; Retno Catur Kusuma Dewi (UNES Law Review, 2023)
Franchise is a form of business that is growing and popular in today's business world. However, this business also requires strong legal protection, especially regarding copyright. This study aims to analyze the legal protection of franchisors and franchises from a copyright perspective. The research method used is an inductive qualitative method. The results of the study show that legal protection for franchisors and franchisors from a copyright perspective is very important to prevent copyright infringement and ensure business continuity. In the perspective of Indonesian law, the Copyright Law provides strong legal protection for franchisors and franchisors. However, there are still challenges and problems in implementing this legal protection, such as a lack of awareness and understanding of copyright. Therefore, more serious efforts are needed from related parties, such as business owners, government and related institutions, to increase awareness and understanding of legal protection of franchising and franchising from a copyright perspective.